(E,E)-1,2-Bis[3-methoxy-4-(prop-2-yn-1-yl-oxy)benzylidene]hydrazine - Al-Mehana, W.N.A.; Shakir, R.M.; Yahya, R.; Abd Halim, S.N.; Tiekink, E.R.T. (2011)
The complete mol-ecule in the title compound, C 22H 2N 2O 4, is generated by the application of an inversion centre. With the exception of the terminal acetyl-ene groups C - O - C - C = -78.02 (17)Â°, the remaining atoms constituting the mol-ecule are essentially coplanar. The configuration around the C=N bond 1.282 (2) Ã is E. The formation of supra-molecular chains mediated by C - Hâ¯O inter-actions, occurring between methyl-ene H and meth-oxy O atoms, is the most notable feature of the crystal packing.